2022
DOI: 10.1038/s41598-022-05805-8
|View full text |Cite
|
Sign up to set email alerts
|

Elution profile of cationic and anionic adsorbate from exhausted adsorbent using solvent desorption

Abstract: Present invention involves to study the elution profile of anionic and cationic compounds from exhausted adsorbents using various eluents. Batch elution studies of anionic components like Congo Red dye and Carbonate ion; and cationic compounds such as Methylene blue dye and Cadmium metal from previously used naturally prepared adsorbents i.e. Gulmohar (Delonix regia) leaf powder—GLP; and Neem (Azadirachta indica) leaf powder—NLP and their derivatives were conducted. Different eluents used for batch study were … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Generally, NaOH has a higher cation exchange capacity and loses its solvation easily during the ion-exchange process. At equilibrium, the quantity of adsorbent is higher than adsorbate 102 , hence when the cations present in the exhausted PA-12/PC nanocomposite were reacted with negatively charged NaOH, the anionic CR desorbed from exhausted PA-12/PC nanocomposite due to electrostatic interaction. This observation confirms the isotherm results that adsorption is dominated by physical adsorption.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, NaOH has a higher cation exchange capacity and loses its solvation easily during the ion-exchange process. At equilibrium, the quantity of adsorbent is higher than adsorbate 102 , hence when the cations present in the exhausted PA-12/PC nanocomposite were reacted with negatively charged NaOH, the anionic CR desorbed from exhausted PA-12/PC nanocomposite due to electrostatic interaction. This observation confirms the isotherm results that adsorption is dominated by physical adsorption.…”
Section: Resultsmentioning
confidence: 99%
“…This result confirms that an increase in the concentration of acid increases the desorption of heavy metals. However, it has been reported that a higher concentration of acid above 0.15 mol L −1 may damage the structure of the adsorbent 28 …”
Section: Resultsmentioning
confidence: 99%
“…However, it has been reported that a higher concentration of acid above 0.15 mol L −1 may damage the structure of the adsorbent. 28…”
Section: Thermodynamic Evaluation Of Adsorption Processmentioning
confidence: 99%
See 2 more Smart Citations